SUGGESTED SOLUTIONS FOR SUSTAINABLE MANAGEMENT OF MANGROVES AND SEAGRASS BEDS AT THUY TRIEU LAGOON - Thuy, Nguyen Thi Thanh; Tuan, Vo Si; Hoa, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2014)
Based on the relevant studies and successful results obtained from two mangrove restoration models at aquaculture area and intertidal zone of the lagoon, solutions for sustainable management of mangroves and seagrass beds of the lagoon have been suggested including (1) Heightening community awareness of mangrove - seagrass ecosystems; (2) Setting up a volunteer guard team; (3) Remarkable priority zoning in terms of function including: (a) Zone for mangrove restoration and seagrass bed management at the top of the lagoon (b) Cam Hai Dong remarkable biodiversity conservation zone (c) Mangrove restoration zone at Cam Thanh Bac tidal zone. Each remarkable functional zone corresponds with the specific aim and community-based management, in which the duties, responsibilities of the relevant members are attached to their benefits from sustainable management of mangroves and seagrass bed at Thuy Trieu lagoon.